2019
DOI: 10.7150/jca.29916
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulated of Angiopoietin-Like Protein 4 Predicts Poor Prognosis in Cervical Cancer

Abstract: Background: Angiopoietin-like protein 4 (ANGPTL4) has been demonstrated highly expressed in some cancers, but it also was downregulated in others through DNA methylation. However, the expression status of ANGPTL4 in cancer of cervix remains unclear. Thus, our present study attempts to investigate the role of ANGPTL4 in the prognosis of patients with cervical cancer. Methods: Immunohistochemistry, western blotting and qRT-PCR were performed to investigate the expressive level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Previous studies demonstrated that ANGPTL4 was associated with a variety types of cancers such as osteosarcoma, 16 gastric cancer, 17 renal cell carcinoma, 18 non-small cell lung cancer, 19 and cervical cancer, 20 and played pivotal roles in tumor growth, proliferation and metastasis. 21 ANGPTL4 was identified as a factor of lipid metabolism and angiogenesis which could be regulated by the nuclear hormone receptors PPARs, hypoxic conditions, fasting, and transforming growth factor β.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that ANGPTL4 was associated with a variety types of cancers such as osteosarcoma, 16 gastric cancer, 17 renal cell carcinoma, 18 non-small cell lung cancer, 19 and cervical cancer, 20 and played pivotal roles in tumor growth, proliferation and metastasis. 21 ANGPTL4 was identified as a factor of lipid metabolism and angiogenesis which could be regulated by the nuclear hormone receptors PPARs, hypoxic conditions, fasting, and transforming growth factor β.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] More importantly, ANGPTL4 was suggested to be a novel diagnostic and prognostic biomarker for patients with renal cell carcinoma or cervical cancer. 20,30 However, no reports have investigated the role of ANGPTL4 in PTC. Therefore, this study further explores the possibility of ANGPTL4 as a potential molecular target for thyroid cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of ANGPTL4 reportedly suppresses adenylate energy charge elevation, thus delaying EMT [26]. Upregulation of ANGPTL4 is associated with a poor prognosis of cancers and promotes tumor cell proliferation and migration, including OS cells [27,28]. STC1, as well as STC2, was originally identified as a calcium/phosphate-regulating hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of ANGPTL4 reportedly suppresses adenylate energy charge elevation, thus delaying EMT [26]. Upregulation of ANGPTL4 is associated with a poor prognosis of cancers and promotes tumor cell proliferation and migration, including OS cells [27,28]. STC1, as well as STC2, was originally identi ed as a calcium/phosphate-regulating hormone.…”
Section: Discussionmentioning
confidence: 99%